(untitled) (Anwer Khan Modern Medical College Journal, 2013)
Association of fasting plasma glucose (FPG) and post prandial plasma glucose (PPG) on hemoglobin glycation is still controversial. In this study we aimed to assess the influence of FPG and PPG on hemoglobin glycation in newly diagnosed never treated diabetic (NDNT-DM) subjects and treated diabetic (T-DM) subjects. One hundred and seventy seven diabetic subjects were included in this study. Plasma glucose concentrations were measured by hexokinase end point technique and glycated hemoglobin (HbA1c) levels were measured by modified cationexchange high performance liquid chromatography (HPLC). Univariate and multivariate linear regression models were applied to assess the relative contribution of FPG and PPG on HbA1c. Univariate linear regression analysis showed significant positive association of FPG and PPG with HbA1c in both groups. Multivariate regression model showed that ? (beta) value of HbA1c was 0.5528 (p<0.0001) for FPG and 0.3047 (p<0.01) for PPG in the NDNT-DM whereas 0.5509 (p<0.0001) for FPG and 0.1874 (p>0.05) for PPG in treated diabetic subjects. After adjustment for age and sex, beta remains statistically significant for FPG and PPG where beta value for FPG was higher for FPG than for PPG in both NDNT-TM group and T-DM groups. This study revealed that FPG has a stronger association on hemoglobin glycation as compared to PPG in diabetes mellitus. Anwer Khan Modern Medical College Journal Vol. 4, No. 2: July 2013, Pages 28-30 DOI: http://dx.doi.org/10.3329/akmmcj.v4i2.16939